Science, explanation, and rationality : aspects of the philosophy of Carl G. Hempel - Fetzer, James H., 1940- (OUP E-Books., 2000)
The late Carl Hempel was one of, if not the most influential philosophers of science in the 20th century. His work defined the problems and the methodology of the discipline for over thirty years. In this volume, thirteen highly distinguished philosophers, most of whom studied with Hempel, illuminate and clarify the central problems to which Carl G. Hempel was devoted. The result enhances our understanding of major developments in the philosophy of science, particularly the development of logical empiricism as a major - even the major - intellectual influence for scientifically-oriented philosophers and philosophically-minded scientists during the 20th century. It should appeal to an unusually broad audience of students and scholars of the philosophy of science, of the history of philosophy, and of 20th century intellectual history.